2017
DOI: 10.1101/210187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved maternal-specific repressive domain in Zelda revealed by Cas9-mediated mutagenesis inDrosophila melanogaster

Abstract: In nearly all metazoans, the earliest stages of development are controlled by maternally deposited mRNAs and proteins. The zygotic genome becomes transcriptionally active hours after fertilization. Transcriptional activation during this maternal-to-zygotic transition (MZT) is tightly coordinated with the degradation of maternally provided mRNAs. In Drosophila melanogaster, the transcription factor Zelda plays an essential role in widespread activation of the zygotic genome. While Zelda expression is required b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 45 publications
(91 reference statements)
2
21
0
Order By: Relevance
“…CP190), and displays extensive H3K27me3 marks as well as several prominent Zelda peaks (Fig. 1b) [50][51][52][53] . At nc14, the Hi-M contact probability map of this genomic region displays two clear TADs, similar to those detected by Hi-C (TAD1, and doc -TAD, Figs.…”
Section: High-resolution Hi-m Reveals Preferential Interactions Betwementioning
confidence: 99%
See 1 more Smart Citation
“…CP190), and displays extensive H3K27me3 marks as well as several prominent Zelda peaks (Fig. 1b) [50][51][52][53] . At nc14, the Hi-M contact probability map of this genomic region displays two clear TADs, similar to those detected by Hi-C (TAD1, and doc -TAD, Figs.…”
Section: High-resolution Hi-m Reveals Preferential Interactions Betwementioning
confidence: 99%
“…Inspection of ATAC-seq 54 , H3K4me3, H3K4me1, and H3K27ac profiles 55 as well as of enhancer databases 56 revealed that the doc -TAD contains several putative CRMs, including four potential enhancers (CRM a , CRM b , CRM c and CRM d ) for the three doc promoters (Fig. 1c, Supplementary Table 1) 50,51,56,57 . However, conventional Hi-M/Hi-C did not exhibit specific looping interactions within the doc -TAD, most likely due to insufficient genomic resolution and coverage ( Fig.…”
Section: High-resolution Hi-m Reveals Preferential Interactions Betwementioning
confidence: 99%
“…Cas9-mediated genome engineering as described in (Hamm et al 2017) was used to generate the N-terminal and C-terminal super folder Green Fluorescent Protein (sfGFP)-tagged GAF. The double-stranded DNA (dsDNA) donor was created using Gibson assembly (New England BioLabs, Ipswich, MA) with 1-kb homology arms flanking the sfGFP tag and GAF N-terminal or C-terminal open reading frame.…”
Section: Cas9-genome Engineeringmentioning
confidence: 99%
“…Zelda was found to be conserved throughout insects and crustaceans, and examination of a number of species revealed that the protein has additional conserved regions, like an acidic patch (which could be involved in the recruitment of chromatin remodeling proteins) and two N‐terminal Zinc fingers . The functional study of Zelda domains was approached using a Cas9 engineering system to obtain D. melanogaster insects with point mutations in the Zinc finger 1, in the acidic patch, or in the Zinc finger 2 (JAZ) . Mutations in the Zinc finger 1 or in the acidic patch did not affect the viability of the insects, whereas mutations in the Zinc finger 2 (JAZ) led to a maternal‐effect lethal phenotype .…”
Section: Introductionmentioning
confidence: 99%
“…The functional study of Zelda domains was approached using a Cas9 engineering system to obtain D. melanogaster insects with point mutations in the Zinc finger 1, in the acidic patch, or in the Zinc finger 2 (JAZ) . Mutations in the Zinc finger 1 or in the acidic patch did not affect the viability of the insects, whereas mutations in the Zinc finger 2 (JAZ) led to a maternal‐effect lethal phenotype . A transcriptomic analysis of mutated flies showed that the Zinc finger 2 (JAZ) acts as a maternal repressive domain during embryo development, being associated with the transcriptional regulation of the zygotic Zelda targets and with the clearance of maternal transcripts .…”
Section: Introductionmentioning
confidence: 99%